2018
DOI: 10.1007/978-3-319-98812-2_36
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Rainfall and Temperature on Peak and Off-Peak Urban Traffic

Abstract: This paper focuses on quantifying the effect of rainfall and temperature intensities on urban traffic characteristics in peak and off-peak respectively hours using traffic data from Greater Manchester, UK, as a case study. Three broader issues are addressed: (1) the impact of rainfall on urban traffic; (2) the impact of rainfall intensity on traffic flow parameters at both peak and off-peak periods; (3) the impact of atmospheric temperature level on peak and off-peak urban traffic. Our contribution arises both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 14 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…Many studies have examined driver behavior, travel mode, road conditions, and the importance of weather data. For example, in a study [4], rainfall intensity was associated with a 4-9% reduction in traffic. It is also found that traffic congestion has a significant relationship with temperature intensity.…”
Section: Introductionmentioning
confidence: 96%
“…Many studies have examined driver behavior, travel mode, road conditions, and the importance of weather data. For example, in a study [4], rainfall intensity was associated with a 4-9% reduction in traffic. It is also found that traffic congestion has a significant relationship with temperature intensity.…”
Section: Introductionmentioning
confidence: 96%
“…Data-driven techniques for predictive analytics in smart manufacturing can be classified as (traditional) ML techniques and deep learning (DL) techniques [7]. In the literature, many data-driven approaches have been applied toward time-series forecasting or classification, including autoregressive integrated moving average (ARIMA) [8], support vector machines [9], statistical analysis [10], and instance-based learning techniques. The application of traditional ML techniques on large datasets consistently exposes the inherent vulnerabilities of these models, such as the inability to deal with the high dimensionality of the data feature space, multicollinearity, and varying data aggregation [11].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of traffic operation, it is an acknowledged fact that rainfall reduces traffic capacity and operating speeds, thereby increasing congestion and road network productivity loss [8]. For instance, daily weather conditions like fog, heavy rainfall, and snow can reduce travel demand, cause trip postponement or cancellation, or affect travel mode (changing from a slow mode like walking or cycling to a faster one, such as car or train).…”
Section: Introductionmentioning
confidence: 99%